If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -1m = 7 Solving -2 + -1m = 7 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1m = 7 + 2 Combine like terms: -2 + 2 = 0 0 + -1m = 7 + 2 -1m = 7 + 2 Combine like terms: 7 + 2 = 9 -1m = 9 Divide each side by '-1'. m = -9 Simplifying m = -9
| 4x^2=3x^2+9 | | 5(f-4)=-10 | | -5+5x=35 | | (x-2)=-2x-1 | | 8g-32=4g+16 | | X+17+4x=-29-4x-35 | | 1halfr+6=3-2r | | -10(s+3)=-71 | | (5x^3-6x^2+2x)+(-4x^2+3x)=42 | | 35x^2+76x+32= | | -10(s+3)=71 | | (x-5)=-6x-10 | | 3-2x^2=21 | | 10=-0.15x^2+3x | | t+10=7t+4 | | -8+3x=6+x | | 2-o=-42 | | (x-3)=-6x-17 | | -2+12=12 | | 3n+8-8=-3+2n | | x^2+47x=48 | | (x-3)=6x+17 | | 9.4=5.6-d | | 0.3(6x-9)=-27 | | Tv=2v-20 | | 31+12x-32-10x=27+29 | | v=hpir^2 | | 65+y=72 | | -7(m+3)=2(12-6m) | | .15x+.05(2-x)=.10(17) | | 150s(225s-3.50)=2000 | | -2+3x=-5 |